Is molecular gas necessary for star formation? - Glover, Simon; Clark, Paul C. (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. On galactic scales, the surface density of star formation appears to be well correlated with the surface density of molecular gas. This has led many
Gesehen am 31.08.2018